Analysis of image quality based on dentists' perception cognitive analysis and statistical measurements of intra-oral dental radiographs - Siti Arpah, Ahmad; Mohd Nasir, Taib, Prof. Dr.; Noor Elaiza, Abd. Khalid; Haslina, Taib, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/